Improved detectability of sex steroids from frozen sections of breast cancer tissue using GC-triple quadrupole-MS. Issue 178 (April 2018) - Moon, Ju-Yeon; McNamara, Keely May; Lee, Jung-Jin; Chung, Bong Chul; Sasano, Hironobu; Choi, Man Ho
Graphical abstract: Highlights: Sex steroids were measured from trace amounts of tissue samples. Extractable alkyloxycarbonylation improved chromatographic properties. Pentafluroropropionylation produces characteristic ions in mass spectrometry. GC–MS/MS resulted in a sensitive detection of sex steroids from frozen breast tissue slices. Abstract: Sex steroids in clinical endocrinology have been mainly investigated with peripheral blood and urine samples, while there is limited information regarding the local levels within tissues. To improve analytical properties of sex steroids from trace amounts of tissue samples, two-phase extractive ethoxycarbonlyation and subsequent pentafluoropropionyl derivatization coupled to gas chromatography–tandem mass spectrometry (GC–MS/MS) was developed. The optimized analytical conditions led to excellent chromatographic separation of 15 estrogens, 6 androgens, and 2 progestins. The quantitative results were calculated based on in-house control samples as the steroid-free tissues, and the precision and accuracy were 4.2%–26.8% and 90.8%–116.4%, respectively. The on-column limit of quantification was from 180 fg to 0.5 pg for androgens and estrogens, and 1.25 pg for progestins, which were found to be linear ( r 2  > 0.990). The validated method was then applied to quantify 7 sex steroids from three 100-μm-thick frozen breast tissue slices from postmenopausal patients with breast cancer. This is the first report on the improved GC–MS/MS method for the detection of androgens and pregnenolone from breast cancer tissues, and it can be a useful technique to measure the local levels of sex steroids, thus, enhancing our understanding of the pathophysiological significances of steroidogenesis.